Real‐Space Interpretation of Interatomic Charge Transfer and Electron Exchange Effects by Combining Static and Kinetic Potentials and Associated Vector Fields. Issue 48 (6th July 2022) - Shteingolts, Sergey A.; Stash, Adam I.; Tsirelson, Vladimir G.; Fayzullin, Robert R.
Abstract: Intricate behaviour of one‐electron potentials from the Euler equation for electron density and corresponding gradient force fields in crystals was studied. Channels of locally enhanced kinetic potential and corresponding saddle Lagrange points were found between chemically bonded atoms. Superposition of electrostatic ϕ e s r and kinetic ϕ k r potentials and electron density ρ r allowed partitioning any molecules and crystals into atomic ρ ‐ and potential‐based ϕ ‐basins; ϕ k ‐basins explicitly account for the electron exchange effect, which is missed for ϕ e s ‐ones. Phenomena of interatomic charge transfer and related electron exchange were explained in terms of space gaps between zero‐flux surfaces of ρ ‐ and ϕ ‐basins. The gap between ϕ e s ‐ and ρ ‐basins represents the charge transfer, while the gap between ϕ k ‐ and ρ ‐basins is a real‐space manifestation of sharing the transferred electrons caused by the static exchange and kinetic effects as a response against the electron transfer. The regularity describing relative positions of ρ ‐, ϕ e s ‐, and ϕ k ‐ basin boundaries between interacting atoms was proposed. The position of ϕ k ‐boundary between ϕ e s ‐ and ρ ‐ones within an electron occupier atom determines the extent of transferred electron sharing. The stronger an H⋅⋅⋅O hydrogen bond is, the deeper hydrogen atom's ϕ k ‐basin penetrates oxygen atom's ρ ‐basin, while for covalent bonds a ϕ k ‐boundary closely approaches a ϕ e s ‐one indicating almost complete sharing of the transferred electrons. In the case of ionic bonds, the same region corresponds to electron pairing within the ρ ‐basin of an electron occupier atom. Abstract : Phenomena of interatomic charge transfer and consequent electron exchange were explained in terms of space gaps between the zero‐flux surfaces of atomic and electrostatic and kinetic potential‐based basins. Behaviour of one‐electron potentials included in the Euler equation for electron density and corresponding gradient force fields in crystals was studied.